Hubungan Sumber Informasi, Asupan Gizi, dan Dukungan Keluarga Terhadap Tumbuh Kembang Bayi 0-12 Bulan di Puskesmas Maripari Tahun 2023 - Winarti, Winda; Hayatullah, Madinah Munawaroh; Kusumastuti, Istiana (Madani: Jurnal Ilmiah Multidisiplin, 2024)
Growth and development can be influenced by good nutritional intake, parenting patterns, sources of information and also family support, most of which nutritional intake has a very significant effect on the growth and development of babies 0-12 months. The aim of this research is to determine the relationship between sources of information, nutritional intake and family support on the growth and development of babies 0-12 months at the Maripari Community Health Center in 2023 using quantitative research methods, and the research design used is analytical descriptive with a sample size of 54 respondents. The results of the Chie Square test, there is a significant relationship between the source of information on the growth and development of babies 0-12 months with a p value of 0.027, there is a significant relationship between nutritional intake and the growth and development of babies 0-12 months with a p value of 0.0000, and there is a There is a significant relationship between family support and the growth and development of babies 0-12 months with a p value of 0.014. Conclusion: Nutritional intake has the greatest influence on the growth and development of babies 0-12 months, it is recommended for mothers or respondents to be smarter in processing food or give food to the baby.